Epidemiological study of neural tube defects in Jammu division, India - Singh, Virender; Raina, Sachi; Dewan, Deepika; Raina, Sunil; Dogra, Vikram (International Journal of Research in Medical Sciences, 2019)
Background: Prevalence and spectrum of neural tube defects has undergone seasonal and secular variations in different regions of the world since the turn of last century. However precise etiology inspite of lot of research has not been clearly elucidated. Methods: The study was conducted in Government Medical College Hospital and SMGS Hospital Jammu in patients diagnosed to have a neural tube defect from birth to 19 years. History regarding sociodemographic profile, antenatal history and significant birth history was elicited. Complete general physical examination, Local examination of the lesion was carried out and neural tube defects were classified. All the cases were subjected to ultrasound head to determine ventricular size and rule out hydrocephalus. The data was entered in Microsoft Excel and results were presented in form of percentages and proportions. Results: Maximum children admitted were in the age group of <1 month and belonged to Jammu district. Commonest anomaly seen was lumbosacral meningomyelocele with associated hydrocephalus and neural deficit. Mothers who gave birth to an NTD affected child were commonly in the age group of 20-30 years, with commonest NTD affected sib being 1stborn and most of parents being from very low socio-economic strata of society. Only 7 mothers had received antenatal advice with ultrasound and almost none had received folic acid either before or after conception. Conclusions: Neural tube defects appear to be fairly common anomaly among females of lower socioeconomic strata, living in far flung mountainous regions of the state, devoid of proper health care facilities and education.